Pengaruh Pembiayaan Mikro terhadap Perkembangan UMKM Nasabah BSI KCP Mojopahit 2 - Rachmawati, Desy Wulan; Yasin, Ach (Jurnal Ekonomika dan Bisnis Islam, 2022)
The development of MSMEs in Indonesia is not free from problems, some of the problems generally experienced by MSMEs are limited sources of capital, the difficulty of raw materials that are affordable but of high quality, limited knowledge and technology, market and marketing information, and the quality of human resources. However, most of the problems faced by MSMEs have serious problems in terms of funding or capital which are difficult to obtain so that MSMEs cannot develop a larger market. From these various problems, Bank Syariah Indonesia launched a micro financing program which is capital or investment aimed at micro, small, and medium enterprises in the productive business sector. The purpose of this research is to see and determine the effect of microfinance on the development of MSME customers of BSI KCP Mojopahit 2. The type of research used in this study is quantitative research whose data is obtained from microfinance customers of BSI KCP Mojopahit 2 for the 2022 period. The results of this study indicate that the variable X has an effect on the Y variable. Micro-financing has a positive and significant effect on the development of MSME customers of BSI KCP Mojopahit by 0.292. So, if microfinance increases, the development of MSMEs also increases.